Campus landscape environment for student with disabilities (SwDs)in IIUM - Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Zaidin, Nurbazliah; Mohd Shahli, FitryNadia (IIUM Press, 2016)
The purpose of the study is to provide an understanding on the needs of students with disabilities (SwDs) and their problems in higher educational level. This study is aimed to review a campus landscape environment for SwDs including their support facilities. Preliminary research identifies challenges in providing an accessible built environment in higher educational institution. The literatures are reviewed from type of disabilities, their problems and needs. Data collection use qualitative approach which focussing on barriers faced by SwDs in higher educational level. It is important to understand the need of SwDs before making any decisions. Good campus physical environments can be understood better and improved by greater sensitivity to their nonverbal communications, by increasing designs and spaces that give a sense of comfort and security for SwDs user. Thus, the findings provide a platform for the related organization to identify the needs of SwDs in the educational institution for their support facilities and services in order to help them survive in higher education level. In addition, SwDs will have the same opportunity with others to enter higher educational level. As the conclusion, the study proved that proper campus landscape planning and design is very significant in supporting SwDs needs in terms of their accessibility, usability, and safety within the campus environment. Thus, careful consideration of landscape planning and design must be given higher priority in campus development in order to cater SwDs needs.